2020
DOI: 10.1007/s00464-020-08107-0
|View full text |Cite
|
Sign up to set email alerts
|

A nomogram illustrating the probability of anastomotic leakage following cervical esophagogastrostomy

Abstract: Background Early diagnosis of anastomotic dehiscence following cervical esophagogastrostomy may become difficult. Estimation of an individual probability could help to establish preventive and diagnostic measures. The predictive impact of epidemiological, surgery-related data and laboratory parameters on the development of anastomotic dehiscence was investigated in the immediate perioperative period. Methods Retrospective study in 412 patients with cervical esophagogastrostomy following esophagectomy. Epidem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The low concentrations of Alb and prealbumin on POD 4-6 are identified as potential risk factors for AL. Five studies evaluated postoperative Alb in relation to AL but only Noble reported a significant association with a POD 5 cut-off < 22.5 g/L with fair performance (AUC 0.742) [14][15][16][27][28][29][30]. Our analyses identified an equally fair performance for Alb with threshold values of <24.5 on POD 2 (AUC 0.710) and <26.5 g/L on POD 4 (AUC 0.799).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The low concentrations of Alb and prealbumin on POD 4-6 are identified as potential risk factors for AL. Five studies evaluated postoperative Alb in relation to AL but only Noble reported a significant association with a POD 5 cut-off < 22.5 g/L with fair performance (AUC 0.742) [14][15][16][27][28][29][30]. Our analyses identified an equally fair performance for Alb with threshold values of <24.5 on POD 2 (AUC 0.710) and <26.5 g/L on POD 4 (AUC 0.799).…”
Section: Discussionmentioning
confidence: 73%
“…Elevated CRP levels are the most commonly identified markers for post-esophagectomy complications [14][15][16][17][18][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. CRP is an acute-phase protein synthesized in the liver in response to endotoxins, and its levels commonly increase within 6 h after the onset of the inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Due to uneven needle spacing and ligation intensity, the blood microcirculation around the anastomosis is damaged, and there is still controversy in the prevention and reduction of anastomotic leakage. A nomogram prediction model study found that manual anastomosis was a high-risk factor for increasing anastomotic leakage of cervical esophagogastrostomy [ 9 ]. Another retrospective study found that esophagogastric anastomotic leakage was 14.67% in the manual anastomosis group and 5.33% in the stapler anastomosis group [ 10 ].…”
Section: Discussionmentioning
confidence: 99%